EFFICIENCY OF INNOVATIVE TECHNOLOGIES IN THE ORGANIZATION OF THE EDUCATIONAL PROCESS - Baiganova, А.М.; Nauryzova , Н.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article is devoted to a close analysis of innovative technologies, with many new types. The choice and use of innovative technologies is made by the decision of the teacher and directly depends on the professional qualification of the teacher. The main tasks of new innovative technologies are: obtaining knowledge, forming skills of independent work, developing the abilities of each student to the extent that they can choose the direction that best corresponds to their knowledge and skills. With the use of new innovative technologies, training aims to improve the efficiency and quality of all levels of the educational process. In accordance with this, education using new innovative technologies is the main task today. The purpose of the article is to demonstrate the ways of effective selection and application of new innovative technologies aimed at the formation of competencies in an educational institution.